A Process On The Recovery Of RE Minerals With A Chelating Collector - Li Fangi (The Minerals, Metals and Materials Society, 1989)
This paper describes the characteristics and regularities of a process to recover rare earth minerals from Baotou Ore with H-205 collector. H-205 is a kind of hydroxamic acid with amide as a polar group and poly-cycle aromatic hydrocarbon as a non-polar group, having strong ability to capture RE minerals (bastnasite, monazite). When adding a certain dosage of water glass and some other modifying agents, and maintaining pH value between 8.5 and 9.5, RE minerals can be effectively separated from calcium and barium minerals, such as fluorite and barite, etc. Under normal flotation temperature and concentration, when using H-205 to float RE minerals, it needs a bit longer conditioning time (a few minutes longer than that for the conventional collectors). It is also shown that the reagent has the property of resistance to hard water. The laboratory scale and pilot scale tests of the process have been carried out on bulk froth containing RE minerals and fluorite taken from Ore Dressing Plant of Baotou Iron and Steel Company, in both cases, high grade RE concentrates were obtained and the recovery increased remarkably. Therefore, the process has a great practical value.